Dormant Turfgrass Paint and Glyphosate Application Timing Effects on Annual Bluegrass and Tall Fescue Control - J. Hoyle; J. Reeves (Kansas Agricultural Experiment Station Research Reports, 2015)
Excellent annual bluegrass control can be achieved with dormant glyphosate and glyphosate + Endurant treatments applied November through February. The addition of Endurant to glyphosate in early applications (November and December) increases tall fescue control.
Keywords: turfgrass; dormant turfgrass paint; glyphosate; Endurant; tall fescue; annual bluegrass; Poa annua L.; Schedonorus arundinaceus Schreb.; zoysia; spring greenup; Meyer zoysiagrass; Z. japonica Steud.